My unwilling witch gets a makeover - Oram, Hiawyn; Warburton, Sarah (London: Orchard Books, 2010)
Rumblewick, a Highly Qualified Witch's Cat, records in his diary what happens when his reluctant young witch tries to pursue a modeling career on the Other Side.
Keywords: Witches -- Fiction; Cats -- Fiction; Beauty culture -- Fiction; Diaries -- Fiction; Humorous stories